Making woodblock prints - Chesterman, Merlyn; Nelson, Rod (Wiltshire, [England] The Crowood Press, 2015)
"Woodblock printing is an ancient art form, which produces beautiful, subtle and lively prints with just a few simple materials. This book introduces the art, and shares technical information and ideas for those with more experience. Drawing on the vibrant living traditions from China and Japan, it is both a technical guide and an inspiration."' -- Provided by publisher
Chapter 1 An introduction to the woodblock print -- Chapter 2 Materials -- Chapter 3 Equipment and sharpening -- Chapter 4 Getting started -- Chapter 5 Design and cutting a woodblock print -- Chapter 6 Color and inks -- Chapter 7 Registration -- Chapter 8 Proof and print
Includes bibliographical references (page 111) and index.
Keywords: Wood-engraving -- Printing; Wood-engraving -- Technique